Forms of organising in industrial history
1 online resource.
Keywords: "This shortform book presents key peer-reviewed research selected by expert series editors and contextualised by new analysis from each author on different forms of organising British industry. With contributions on the strengths and weaknesses of the holding company structure, government organisation of industry during war time, the effects of forms of organisation on innovation, and debates over the suitability of international comparisons, this volume provides an array of fascinating insights into industrial history. Of interest to business and economic historians, this shortform book also provides analysis and illustrative case-studies that will be valuable reading across the social sciences"--